Profit levels and profitability ratios reported in the communications of public companies - Masztalerz, Marek (Poziomy zysku i wskaźniki rentowności raportowane w komunikatach spółek publicznych, 2019)
The purpose of the article is to identify the scope and to assess the quality of disclosures of profit levels and profitability ratios in the communications of public companies included in the WIG20 index. The research involved analyzing the content posted by companies on websites, such as financial statements, the annual report, chairman’s letter to the shareholders, the presentation of results for investors, and financial highlights published directly on the website. In total, nearly 70 communiques were analyzed. The descriptive analysis method, the comparative analysis and the induction method were used. As a result of the conducted research, it was determined whether and in which communications, and at which levels, the financial results and profitability ratios are reported and what is their frequency in the individual postings. The calculation formulas used between the companies were compared, the uniformity of the formulas used by each company in various messages was verified and their consistency with the reported numbers was checked
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 19-28
Keywords: accounting communication; investor relations; reporting; profit; profitability; komunikacja w rachunkowości; relacje inwestorskie; raportowanie; zysk; rentowność